Phloem 2012
DOI: 10.1002/9781118382806.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Breaching the Sieve Element—The Role of Saliva as the Molecular Interface Between Aphids and the Phloem

Abstract: Aphids (order Hemiptera; suborder Sternorrhyncha) are fast becoming an excellent system for studying molecular interactions between sap feeding insects and their host plants. This has been facilitated, in part, by the recent completion of the pea aphid (Acyrthosiphon pisum) genome project (IAGC, 2010) and the development of high throughput genomic resources such as preliminary genomes and large-scale EST libraries for a number of other aphid species. Coupled with a strong tradition as a model system for invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…Gel saliva forms a salivary flange on the plant surface prior to plant penetration ( Figure 1A ; Will et al, 2012b), which is suggested to stabilize the stylet before initiating stylet penetration of the plant (Pollard, 1973; Tjallingii, 2006). When the stylet moves, small amounts of gel saliva are secreted; these harden and are then penetrated by the stylet (McLean and Kinsey, 1965).…”
Section: “Insects In Action”: How Phloem-feeding Insects Overwhelm Plmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel saliva forms a salivary flange on the plant surface prior to plant penetration ( Figure 1A ; Will et al, 2012b), which is suggested to stabilize the stylet before initiating stylet penetration of the plant (Pollard, 1973; Tjallingii, 2006). When the stylet moves, small amounts of gel saliva are secreted; these harden and are then penetrated by the stylet (McLean and Kinsey, 1965).…”
Section: “Insects In Action”: How Phloem-feeding Insects Overwhelm Plmentioning
confidence: 99%
“…When the stylet moves, small amounts of gel saliva are secreted; these harden and are then penetrated by the stylet (McLean and Kinsey, 1965). This continuous secretion of gel saliva leads to the formation of a solid salivary sheath that envelops the stylet and is left in situ after it is withdrawn from plant tissues (Will et al, 2012b). Sheath formation was assumed to be associated with the oxidation of protein sulphydryl groups, e.g., present in the amino acid cysteine (Miles, 1965; Tjallingii, 2006).…”
Section: “Insects In Action”: How Phloem-feeding Insects Overwhelm Plmentioning
confidence: 99%
See 1 more Smart Citation
“…The intimate relationship between an aphid and its host is mediated by the secretion of abundant amounts of saliva during all the stages of feeding, including probing and ingestion (Will et al 2013). Two types of saliva are secreted during feeding, the "sheath saliva"-once secreted, although initially in liquid form, hardens around the stylet to form a path in the plant cells and remains in the plant; and the second form that remains as a liquid to facilitate feeding-known as "watery saliva."…”
Section: Discussionmentioning
confidence: 99%
“…Aphids typically cause little damage to plant tissue because they use their stylets to navigate in between plant cells [18][19][20]. During this process, aphids inject saliva into the plant [21,22]. One type of saliva, called gelling saliva, is secreted into the apoplastic space where it gelatinizes, and the aphid subsequently pushes its stylet through the gel so that the gel forms a sheath [23].…”
Section: Introductionmentioning
confidence: 99%